Protective Effect of Benzoquinone Isolated from the Roots of Averrhoa carambola L. on Streptozotocin-Induced Diabetic Mice by Inhibiting the TLR4/NF-κB Signaling Pathway - Qin L; Zhang X; Zhou X; Wu X; Huang X; Chen M; Wu Y; Lu S; Zhang H; Xu X; Wei X; Zhang S; et al. (Diabetes, Metabolic Syndrome and Obesity, 2020)
Luhui Qin,1,2,* Xiaolin Zhang,1,* Xing Zhou,1 Xingchun Wu,1 Xiang Huang,1 Ming Chen,1 Yani Wu,1 Shunyu Lu,1 Hongliang Zhang,1 Xiaohui Xu,1 Xiaojie Wei,1 Shijun Zhang,1 Renbin Huang1 1Pharmaceutical College, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 2Center for Translational Medicine, Key Laboratory of Longevity and Aging-Related Diseases, Ministry of Education, School of Preclinical Medicine, Guangxi Medical University, Nanning, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Renbin Huang; Shijun ZhangPharmaceutical College, Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region 530021, People’s Republic of ChinaTel +86 771 533 9805Fax +86 771 535 8272Email huangrenbin518@163.com; gxykdxzsj@163.comBackground: Studies have demonstrated that the roots of Averrhoa carambola L. (Oxalidaceae), a traditional Chinese medicine, can be used to treat diabetes and diabetes-related diseases. Nevertheless, the potential beneficial effects and mechanism of benzoquinone isolated from the roots of Averrhoa carambola L. (BACR) on diabetes remain unclear.Methods: Diabetic Kunming mice were injected with STZ (120 mgkg− 1) in the tail vein. Fasting blood glucose (FBG) and the change of body weight were measured after oral administration of BACR (120, 60, 30 mg/kg/d) every week. The levels of the total cholesterol (TC), triglyceride (TG), free fatty acids (FFA), glucosylated hemoglobin (GHb), fasting insulin (FINS), tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were measured. The histological examination of pancreatic tissues and the TLR4/NF-κB pathway was analyzed by RT-PCR, immunohistochemistry and Western blot.Results: The study found that clearly the BACR obviously reduced the blood glucose, serum lipids, GHb and FINS. In addition, BACR treatment markedly reduced the release of inflammatory factors, including IL-6 and TNF-α, and down-regulated the expression of the TLR4/NF-κB pathway.Conclusion: BACR has potential benefits for the treatment of diabetes by ameliorating metabolic functions and attenuating the inflammatory response via inhibition of the activation of theTLR4/NF-κB pathway.Keywords: benzoquinone of Averrhoa carambola L. root, diabetes, inflammation, TLR4/NF-κB pathway